2018
DOI: 10.1063/1.5060638
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a-Si thin film on the performance of a-Si/ZnO-stacked piezoelectric energy harvesters

Abstract: In this letter, we present the fabrication and characterization of a zinc oxide (ZnO)-based nanogenerator for piezoelectric micro-energy harvesting by combining thin films of amorphous silicon (a-Si) and ZnO. We utilized the a-Si thin film as an interlayer to assemble several a-Si/ZnO-stacked piezoelectric nanogenerators (SZPNGs) on indium tin oxide (ITO)-coated polyethylene naphthalate substrates. We investigated the influence of the a-Si layer thickness on the output voltages of the SZPNGs and demonstrated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In particular, the sample B of the Ag/ZnO/AlN/Cr/ITO/Al-foil structure showed the highest output voltage. Similarly to other reports [12][13][14], we fabricated additional devices including each material (AlN, SiO 2 , or a-Si) used in our earlier researches for a further study, as shown in Figure 10. Here, each target of AlN (5N, iTASCO), n-type a-Si (5N, iTASCO), or SiO 2 (4N, iTASCO) were used to fabricate the devices shown in Figure 10.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, the sample B of the Ag/ZnO/AlN/Cr/ITO/Al-foil structure showed the highest output voltage. Similarly to other reports [12][13][14], we fabricated additional devices including each material (AlN, SiO 2 , or a-Si) used in our earlier researches for a further study, as shown in Figure 10. Here, each target of AlN (5N, iTASCO), n-type a-Si (5N, iTASCO), or SiO 2 (4N, iTASCO) were used to fabricate the devices shown in Figure 10.…”
Section: Resultsmentioning
confidence: 99%
“…For the ZnO deposition in particular, a mixture of 18 sccm Ar and 12 sccm N 2 O gas was flowing during the sputtering process to reduce the free-carrier concentration in the ZnO film, leading directly to the improvement of device performance [16]. Many previously reported devices fabricated on flexible plastic substrates [10,[12][13][14]16,17] have an intrinsic limitation to increasing process temperatures. Thus, in this work, instead of flexible plastic substrates, we have attempted to employ the Al-foil as a substrate to further increase the process temperatures, which helpfully allows for annealing heat treatments at higher temperatures.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations